Neo-Gothic in Croatian Architecture of 19th and Early 20th Century - Damjanović, Dragan (Array, 2012)
The use of Neo-Gothic spread in Croatian architecture as late as the 1850s and 1860s, replacing gradually the previously dominant classicism. From the mid-1870s it began to be predominantly used for Catholic and Protestant church architecture in Croatia owing to the projects by Viennese architect Friedrich von Schmidt and his students, most importantly Herman Bollé and Josip Vancaš. These projects introduced Pugin’s ideas in Croatian architecture for the first time. Pugin’s influence was, however, more an exception than a rule. The biggest number of Neo-Gothic designs drew upon buildings on the European continent (those of Viollet-le-Duc’s, and the Cologne Cathedral architects’). Strong influence was also exerted by architects from Austria-Hungary, especially from Vienna, where the majority of Croatian architects studied in the late 19th century. Neo-Gothic was significant primarily for the Catholic Church which used it to distinguish its buildings from Orthodox Neo-Byzantine churches or synagogues built mostly in the Neo-Moorish style. Since Catholicism was an important part of Croatian national identity there were endeavours, though unsuccessful ones, to make (Neo-)Gothic the basis for a particular national architectural style. Croatian architecture of the second half of the 19th century can enrich the historical context of Neo-Gothic on the European mainland with several accomplishments. Especially interesting are Bollé’s restoration of the Greek Catholic Cathedral in Križevci in the mixed Neo-Gothic and Neo-Byzantine style and the restoration of the Zagreb Cathedral which was a radical attempt in establishing its assumed original Gothic state by removing almost all Baroque architectural elements and furniture.